2007
DOI: 10.1503/cmaj.060962
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of waiting for cataract surgery: a systematic review

Abstract: Background: Cataract surgery is the most common operative procedure performed in Canada, and how patients are affected by wait times for this surgery has important clinical, public health and health policy considerations. We conducted a systematic review to understand the relation between wait time for cataract surgery and patient outcomes and the variables that modify this relation. Methods:We performed an electronic search of 11 databases and the proceedings of 4 conferences. The search was restricted to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 31 publications
0
93
1
4
Order By: Relevance
“…55 Fewer patients who received expedited surgery fell two or more times compared with the group still awaiting surgery (18% (28/154) vs 25% (38/152), P ¼ 0.04).…”
Section: Cataracts and Fallsmentioning
confidence: 93%
“…55 Fewer patients who received expedited surgery fell two or more times compared with the group still awaiting surgery (18% (28/154) vs 25% (38/152), P ¼ 0.04).…”
Section: Cataracts and Fallsmentioning
confidence: 93%
“…[1][2][3][4] Not surprisingly, cataract surgery by phacoemulsification and intraocular lens (IOL) implantation is the most commonly performed surgical procedure worldwide. 3,[5][6][7] Valid evaluation of cataract and its visual consequences is indispensable for the purpose of investigating possible risk factors for cataract formation and for documenting progression of cataract in epidemiologic and cohort studies. Also, reliable and valid assessment of cataract and its visual sequelae is equally important for clinical practice, if the ophthalmologist is to accurately evaluate the impact of age-related cataract on patient's visual performance and experience, and therefore identify those who are likely to benefit from surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…8 A systematic review found that patients who wait more than 6 months for cataract surgery had an increased rate of falls. 9 Furthermore, cataracts have been found to be the most common cause of fracturerelated visual impairment, 10 with untreated cataract causing up to 49% of visual impairment in patients with femoral neck fractures related to decreased vision. 10 Despite the association of poor vision and cataracts with increased fall and fracture risk, only a limited number of studies [11][12][13][14][15] have examined the influence of cataract surgery on fall incidence in visually impaired adults, and only 2 of these studies 11,12 examined the incidence of fractures secondary to falls.…”
mentioning
confidence: 99%